Effectively enhancing the enantioseparation ability of β-cyclodextrin derivatives by de novo design and molecular modeling. Issue 19 (29th August 2017) - Li, Linwei; Wu, Chengjun; Ma, Yang; Zhou, Shuhao; Li, Zhen; Sun, Tiemin
Abstract : A novel strategy to improve the enantioseparation ability of β-cyclodextrin derivatives. Abstract : Rational engineering of native β-CD as an ideal chiral selector for a definite analyte in capillary electrophoresis represents a challenge in separation science. Herein, a rational and systematic strategy that combines the de novo design and molecular modeling is firstly described to expedite the manipulation and selection of effective selector for enantioseparation in capillary electrophoresis. Using β-adrenoreceptor agonists as model analytes, we demonstrate how this strategy efficiently improves the enantiorecognition in chiral discrimination sites of inclusion complexes. The evolved β-CD derivative could be utilized as a chiral receptor to achieve the effective enantioseparation ( R s > 1.5) of racemic β-adrenoreceptor agonists. We highlight a novel strategy for efficiently and rapidly manipulating native CD based on the characteristics of analyte so as to gain an excellent chiral selector.